Impact of Depressive Symptomology on Pain and Function during Recovery after Total Joint Arthroplasty. Issue 8 (August 2021) - Beaupre, Lauren A.; Kang, Sung H.; Jhangri, Gian S.; Boettcher, Tyson; Jones, C. Allyson
Abstract: Objectives: To determine the effect of preoperative depressive symptoms on patient-reported function and pain following total joint arthroplasty (TJA) after controlling for potential confounding factors; how depressive symptoms changed after TJA; and the impact of postoperative depressive symptoms on recovery. Methods: A prospective cohort study undertaken in a metropolitan region in Canada enrolled 710 participants; 622 (87%) had complete 6-month data. Participants completed standardized measures preoperatively and at 1, 3, and 6 months postoperatively. The primary outcome was Western Ontario McMaster Osteoarthritis Index (WOMAC) pain and function. Three groups were created: depressive symptoms absent (n = 573, 82%), possible depressive symptoms (n = 58, 8%), and probable depressive symptoms (n = 68, 10%) using the Center for Epidemiologic Scale for Depression score. Risk-adjusted analyses examined the association between WOMAC change and the preoperative Center for Epidemiologic Scale for Depression score. Results: After risk adjustment, preoperative possible and probable depressive symptomology was associated with postoperative WOMAC pain scores that were 7.6 and 11.7 points, respectively, worse and WOMAC function scores that were 8.8 and 14.3 points, respectively, worse than those without preoperative depressive symptoms. Depressive symptoms improved postoperatively; by 6 months post-TJA, only 34 (5%) participants screened as having probable depressive symptoms, whereas only 13(2%) had possible depressive symptoms. Postoperative WOMAC pain and function scores improved, but they were negatively affected by possible and probable depressive symptoms. Conclusions: Although depressive symptoms improve postoperatively, preoperative depressive symptoms, especially for those with probable depressive symptomology, may negatively affect postoperative pain and functional recovery even after risk adjustment. Abstract : Depressive symptomology is common in those who undergo total joint arthroplasty. This article evaluates the impact of depressive symptomology on postoperative outcomes and recovery as well as how preoperative depressive symptomology changed after surgery.